A yeast excision-repair gene is inducible by DNA damaging agents. - Robinson, G W (1986)
Plasmids containing various RAD-lacZ gene fusions were integrated into the chromosome of haploid yeast cells. These integrant strains were tested for expression of Escherichia coli beta-galactosidase after treatment with agents that damage DNA or interfere with normal DNA replication. We did not observe induction of single-copy RAD1-lacZ or RAD3-lacZ fusion genes under the experimental conditions used. However, exposure of cells containing an integrated RAD2-lacZ fusion gene to UV-radiation, gamma-radiation, 4-nitroquinoline 1-oxide, or nalidixic acid resulted in 4- to 6-fold enhanced expression of beta-galactosidase. Induction of the RAD2 gene after treatment of untransformed cells with 4-nitroquinoline 1-oxide was confirmed by direct examination of RAD2 mRNA. Lower levels of induction (approximately equal to 50%) were observed after treatment of cells with other chemicals. Induction of the RAD2-lacZ fusion gene was also observed in cells transformed with single-copy and multicopy autonomously replicating plasmids.